Pengaruh Tabata Workout Untuk Menjaga Kebugaran Tubuh Pada Masa Pandemi Covid-19 - Nuzularachmania, Firdausi; Indarto, Pungki (Universitas Hamzanwadi, 2022)
The purpose of this study was to determine the effect of tabata exercise treatment on maintaining physical fitness of female students of SMPIT Ar Ruhul Jadid during the covid-19 pandemic. The total population to be studied is 22 students. The sample used for the study were students from class VII to class IX. To obtain data in this study, a Harvard Step Test pretest was held at the first meeting. The next meeting was to give tabata training treatment as many as 16 meetings with an intensity of 3 exercises per week. After carrying out the treatment 16 times, the last stage was given a posttest in the form of a Harvard step test. Data collection techniques used are tests and measurements. The test and measurement used in this research is the Harvard Step Test. The analysis used in this study is the t-test (Paired Sample Test). From the statistical analysis data obtained a sig. (2-tailed) 0.000 <0.05, it can be concluded that there is a significant difference between the pretest and posttest groups of the Harvard Step Test. The benefit of this research is to provide an overview for future research